Controlled Release of a Micelle Payload via Sequential Enzymatic and Bioorthogonal Reactions in Living Systems. Issue 19 (29th March 2019) - Porte, Karine; Renoux, Brigitte; Péraudeau, Elodie; Clarhaut, Jonathan; Eddhif, Balkis; Poinot, Pauline; Gravel, Edmond; Doris, Eric; Wijkhuisen, Anne; Audisio, Davide; Papot, Sébastien; Taran, Frédéric
Abstract: A bioorthogonal approach is explored to release the content of nanoparticles on demand. Exploiting our recently described click‐and‐release technology, we developed a new generation of cleavable micelles able to disassemble through a sequential enzymatic and bioorthogonal activation process. Proof‐of‐concept experiments showed that this new approach could be successfully used to deliver the substances encapsulated into micelles in living cells as well as in mice by two complementary targeted strategies. Abstract : Bioorthogonal nano‐explosion : Nanoparticles designed with biorthogonal iminosydnone cleavable linkers can be destroyed on demand to release their content upon reaction with cyclooctynes. This approach of controlled release was successfully used in living cells as well as in mice.